EFFECTS OF FIXED VERSUS RANDOM CONDITION SEQUENCING DURING MULTIELEMENT FUNCTIONAL ANALYSES1. Issue 1 (20th February 2013) - Hammond, Jennifer L.; Iwata, Brian A.; Rooker, Griffin W.; Fritz, Jennifer N.; Bloom, Sarah E.
Abstract It has been suggested that a fixed condition sequence might facilitate differential responding during multielement functional analyses (FAs) by capitalizing on or limiting sequence effects (Iwata, Pace, et al., 1994); however, the effects of condition sequence have not been examined empirically. We conducted fixed‐ and random‐sequence FAs for 7 individuals with developmental disabilities to determine the relative effects that sequence may have on assessment outcomes. Experimental conditions during the fixed sequence were conducted in the following order: ignore, attention, play, and demand; condition order during the random sequence was determined randomly. Results showed that sequence had no influence on the FA outcomes for 3 subjects, whereas differential responding emerged either faster (1 subject) or only (3 subjects) under the fixed sequence for the remaining subjects. These results suggest that the fixed sequence, a simple modification, should be used when conducting multielement FAs to accommodate the influence of establishing operations across assessment conditions.